2012
DOI: 10.4238/2012.october.15.6
|View full text |Cite
|
Sign up to set email alerts
|

Novel SNPs of the mannan-binding lectin 2 gene and their association with production traits in Chinese Holsteins

Abstract: ABSTRACT. The mannan-binding lectin gene (MBL) participates as an opsonin in the innate immune system of mammals, and single nucleotide polymorphisms (SNPs) in MBL cause various immune dysfunctions. In this study, we detected SNPs in MBL2 at exon 1 using polymerase chain reaction single-strand conformation polymorphism analysis and DNA sequencing techniques in 825 Chinese Holstein cows. Four new SNPs with various allele frequencies were also found. The g.1164 G>A SNP was predicted to substitute arginine with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Further, Zhao et al . [ 57 ] with correlation analysis showed that the g.1197 C>A marker was significantly correlated to SCS, and the g.1164 G>A locus had significant effects on SCS, suggesting possible roles of these SNPs in the host response against mastitis in Chinese Holsteins.…”
Section: Immuno-pathogenesismentioning
confidence: 99%
“…Further, Zhao et al . [ 57 ] with correlation analysis showed that the g.1197 C>A marker was significantly correlated to SCS, and the g.1164 G>A locus had significant effects on SCS, suggesting possible roles of these SNPs in the host response against mastitis in Chinese Holsteins.…”
Section: Immuno-pathogenesismentioning
confidence: 99%
“…In the same line, The substantial correlation between SNPs in the MBL and milk somatic cell score (SCS), a significant phenotypic marker of bovine mastitis, has also been noted by other research studies [48,49]. In Chinese Holstein cattle, the genetic variants of the TRAPPC9 and C4A genes were proven to be associated with mastitis resistance [50,51].…”
Section: Mastitis Susceptibility With Immune and Antioxidant Gene Pol...mentioning
confidence: 66%
“…Many studies have indicated the association of SNPs of lectin pathway in the complement genes with different responses to mastitis resistance. For instance, the mutations in the mannan binding lectin 1, mannan binding lectin 2 and complement C4 genes have been associated with mastitis resistance in the Chinese Holstein cattle [4,20,21]. Moreover, MASP2 is another central protease of the lectin pathway.…”
Section: Single Nucleotide Polymorphism Of Masp2mentioning
confidence: 99%